2012
DOI: 10.1039/c2sc20331f
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the origin of stereoinduction in NHC-catalyzed annulation reactions of α,β-unsaturated acyl azoliums

Abstract: The origin of stereoselectivity of NHC-catalyzed annulation reactions of ynals and stable enols was studied with Density Functional Theory. The data suggest that the C-C bond formation is the stereo-determining step. Only the deprotonated pathway (containing an oxy anion and overall neutral species) was found to give rise to discrimination of the competing stereoisomers. This is due predominantly to electrostatic repulsion of the β-stabilizing enolate functionality with the π-cloud of the aryl group in the NHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 41 publications
2
48
0
2
Order By: Relevance
“…On the other hand, DFT computations from Schoenebeck and Bode with a triazolylidene-derived acylazolium ( 149 ) suggest a two-step mechanism beginning with 1,2-addition followed by [3,3]-sigmatropic rearrangement as the key C-C bond formation step (Scheme 132, path B ). 185e,192 In this mechanism, the nucleophile reversibly pre-associates with 149 to form a kinetically competent hemiacetal intermediate (as in Scheme 131). However, a loose ion pair between the nucleophile and the electrophile, as suggested by Mayr and Studer, could not be excluded.…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…On the other hand, DFT computations from Schoenebeck and Bode with a triazolylidene-derived acylazolium ( 149 ) suggest a two-step mechanism beginning with 1,2-addition followed by [3,3]-sigmatropic rearrangement as the key C-C bond formation step (Scheme 132, path B ). 185e,192 In this mechanism, the nucleophile reversibly pre-associates with 149 to form a kinetically competent hemiacetal intermediate (as in Scheme 131). However, a loose ion pair between the nucleophile and the electrophile, as suggested by Mayr and Studer, could not be excluded.…”
Section: Catalysis Involving Acylazolium Intermediatesmentioning
confidence: 99%
“…[5] a,b-unsaturated acyl azoliums may be generated by internal redox reactions of ynals, [6] by nucleophilic additions to acyl fluorides or esters, [7] or from a,b-unsaturated aldehydes in conjunction with an external oxidant. [8] Studies from ourselves [9,10] and Lupton [11] have shown that these electrophilic reactive species can undergo annulation reactions by a Coates-Claisen process in which the nucleophile preassociates with the highly electrophilic ketone of the acyl azolium followed by a sigmatropic rearrangement. [12] The ability of a,b-unsaturated acyl azoliums to also serve as acceptors in conjugate addition reactions [13] implies that they should also be outstanding partners for other nucleophiles, but catalytic reactions involving nucleophiles that cannot also give 1,2-addition products have not been successful to date; the scope of the annulations has remained limited to activated ketones [8,14] and N-unprotected enamines.…”
mentioning
confidence: 99%
“…[12,15] The subtle details of the stereochemical induction of a related reaction has been recently outlined. [10] Lactam formation followed the protonation of enolate IV and effected catalyst turnover to complete the catalytic cycle.…”
mentioning
confidence: 99%
“…Bis jetzt sind diese von Saccharin abgeleiteten cyclischen Imine als Elektrophile [4] bei der NHC-katalysierten, über ein Homoenolat verlaufenden g-Lactam-Bildung aufgetreten, ergaben dabei aber nur schlechte Enantioselektivitäten. [5] a,b-Ungesättigte Acylazoliumionen kçnnen durch interne Redoxreaktionen von Inalen, [6] durch nukleophile Addition zu Acylfluoriden oder Estern [7] oder aus a,b-ungesättigten Aldehyden mithilfe eines externen Oxidationsmittels erzeugt werden.[8] Studien von uns [9,10] und Lupton [11] haben gezeigt, dass diese reaktiven elektrophilen Spezies Anellierungen über einen Coates-Claisen-Prozess eingehen kçnnen, wobei das Nukleophil mit dem hoch elektrophilen Keton des Acylazoliumions präassoziiert und eine sigmatrope Umlagerung eingeht.[12] Die bekannte Fähigkeit von a,b-ungesättigten Acylazoliumionen, auch als Akzeptoren in konjugierten Additionen [13] zu fungieren, impliziert, dass sie auch hervorragende Reaktionspartner für andere Nukleophile sein sollten. Katalytische Reaktionen mit Nukleophilen, die nicht auch 1,2-Additionsprodukte ergeben kçnnen, waren jedoch bis jetzt nicht erfolgreich; die Substratbreite der Anellierung ist limitiert auf aktivierte Ketone [8,14] und N-ungeschützte Enamine.…”
unclassified
“…[12,15] Die Details der stereochemischen Induktion einer verwandten Reaktion wurden kürzlich umrissen. [10] Nach der Protonierung des Enolats IV erfolgt Lactambildung, welche zum Katalysator-Umsatz führt und somit den Katalysezyklus schließt.…”
unclassified